Cold Cas: reevaluating the occurrence of CRISPR/Cas systems in Mycobacteriaceae - Brenner, Evan; Sreevatsan, Srinand (Frontiers in Microbiology, 2023)
Bacterial CRISPR/Cas systems target foreign genetic elements such as phages and regulate gene expression by some pathogens, even in the host. The system is a marker for evolutionary history and has been used for inferences in Mycobacterium tuberculosis for 30 years. However, knowledge about mycobacterial CRISPR/Cas systems remains limited. It is believed that Type III-A Cas systems are exclusive to Mycobacterium canettii and the M. tuberculosis complex (MTBC) of organisms and that very few of the >200 diverse species of non-tuberculous mycobacteria (NTM) possess any CRISPR/Cas system. This study sought unreported CRISPR/Cas loci across NTM to better understand mycobacterial evolution, particularly in species phylogenetically near the MTBC. An analysis of available mycobacterial genomes revealed that Cas systems are widespread across Mycobacteriaceae and that some species contain multiple types. The phylogeny of Cas loci shows scattered presence in many NTM, with variation even within species, suggesting gains/losses of these loci occur frequently. Cas Type III-A systems were identified in pathogenic Mycobacterium heckeshornense and the geological environmental isolate Mycobacterium SM1. In summary, mycobacterial CRISPR/Cas systems are numerous, Type III-A systems are unreliable as markers for MTBC evolution, and mycobacterial horizontal gene transfer appears to be a frequent source of genetic variation.